The 12 November 2017 Mw 7.3 Ezgeleh‐Sarpolzahab (Iran) Earthquake and Active Tectonics of the Lurestan Arc. Issue 2 (16th February 2019) - Nissen, Edwin; Ghods, Abdolreza; Karasözen, Ezgi; Elliott, John R.; Barnhart, William D.; Bergman, Eric A.; Hayes, Gavin P.; Jamal‐Reyhani, Mohammadreza; Nemati, Majid; Tan, Fengzhou; Abdulnaby, Wathiq; Benz, Harley M.; et al.
Abstract: The 12 November 2017 M w 7.3 Ezgeleh‐Sarpolzahab earthquake is the largest instrumentally recorded earthquake in the Zagros Simply Folded Belt by a factor of ∼10 in seismic moment. Exploiting local, regional, and teleseismic data and synthetic aperture radar interferometry imagery, we characterize the rupture, its aftershock sequence, background seismicity, and regional tectonics. The mainshock ruptured slowly (∼2 km/s), unilaterally southward, for ∼40 km along an oblique (dextral‐thrust) fault that dips ∼14°E beneath the northwestern Lurestan arc. Slip is confined to basement depths of ∼12–18 km, resolvably beneath the sedimentary cover which is ∼8 km thick in this area. The gentle dip angle and basement location allow for a broad slip area, explaining the large magnitude relative to earthquakes in the main Fars arc of the Zagros, where shallower, steeper faults are limited in rupture extent by weak sedimentary layers. Early aftershocks concentrate around the southern and western edges of the mainshock slip area and therefore cluster in the direction of rupture propagation, implying a contribution from dynamic triggering. A cluster of events ∼100 km to the south near Mandali (Iraq) reactivated the ∼50° dipping Zagros Foredeep Fault. The basement fault responsible for the Ezgeleh‐Sarpolzahab earthquake probably accounts for the ∼1 km elevation contrast between the Lurestan arc and the Kirkuk embayment but is distinct from sections of the Mountain Front Fault that define frontal escarpments elsewhere in the Zagros. It may be related to a seismic interface underlying the central and southern Lurestan arc, and a key concern is whether or not the more extensive regional structure is also seismogenic. Key Points: The M w 7.3 Ezgeleh‐Sarpolzahab earthquake ruptured a gently dipping oblique fault in the Lurestan arc basement This faulting may be pervasive across the Lurestan arc, though it is unlikely seismogenic everywhere Relocated aftershocks correlate strongly with directivity implying a component of dynamic triggering